Distinguishing clinical features for pseudocellulitis in pediatric inpatients: A retrospective study. Issue 4 (17th June 2022) - Biglione, Bianca; Cucka, Bethany; Chand, Sidharth; Rrapi, Renajd; Gabel, Colleen K.; Song, Sarah; Kroshinsky, Daniela
Abstract: The clinical features of 588 pediatric inpatients admitted with a diagnosis of cellulitis were reviewed with attention to diagnostic accuracy of true cellulitis (95.1%) versus pseudocellulitis (4.9%) and utilization of specialist consultations (28.1% infectious disease, 6.1% dermatology). Laboratory abnormalities were unable to distinguish cellulitis from pseudocellulitis, supporting previous studies that routine laboratory evaluation may be unnecessary for this diagnosis. Higher rates of pseudocellulitis were identified in cases involving specialist consultation by both dermatology (44.8% pseudocellulitis, 4.1% true cellulitis, p  < .001) and infectious disease (48.3% pseudocellulitis, 27.0% true cellulitis, p  = .01). Thus, consultation may improve the diagnostic accuracy of suspected cellulitis among pediatric inpatients.